Solve the system of equations -5x – 2y = 13 and 3x-y = 12 by combining the equations
1 answer:
Answer:
x=1 y =15
Step-by-step explanation:
hopefully correct
-5x-2y=13 (i)
3x-y=12
-y=12-3x
y=-12+3x (ii)
substitute ii into i
-5x-2(-12+3x)=13
-5x +24-6x=13
-11x=-11
x=1
substitute x into ii
y=-12+3(1)
y=15
.
. . x=1 and y =15
You might be interested in
Answer:
374000
Step-by-step explanation:
use a calculator
Answer:
g=x+2
Step-by-step explanation:
Let's solve for g.
gx=x2+2x
Step 1: Divide both sides by x.
gx/x = x2 +2x / x
<u>g=x+2</u>
<u />
Answer:
Option C
Step-by-step explanation:
I just graphed on my TI-84
Hope this helps!
Answer:
x >-33/2
Step-by-step explanation:
-4x < 66
Divide each side by -4, remembering to flip the inequality
-4x/-4 > 66/-4
x >-33/2
With what because I cannot see the math or any subject of the answer you need